WORD-FORMING SYNONYMY AND VARIABILITY - Sultanova Sevara (International Engineering Journal For Research & Development, 2021)
This work describes the theoretical foundations of word-forming synonymy in modern Russian, as well as the issues of the general theory of linguistic variability.